1982
DOI: 10.1001/jama.1982.03320360032026
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Tears of the Anterior Cruciate Ligament and Knee Locking

Abstract: An infrequently considered cause of knee locking in incomplete tear of the anterior cruciate ligament. In this series, 19 locked knees were diagnosed at the time of arthrotomy as isolated incomplete tears of the anterior cruciate ligament. No pathological findings associated with the menisci, patella, or collateral ligaments were evident. In each case, the torn portion of the anterior cruciate ligament was demonstrated to be the mechanism for locking, and locking resolved with excision or repair of the torn po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…(2) Sensitivity and specificity of MRI are limited to 85–95% which may lead to wrong positive and wrong negative results [23, 24]. This has to be considered, even if Ihara reported very good validity of MRI to diagnose ACL lesions [3, 11, 25–27]. Arthroscopy as the current diagnostic gold-standard was not authorized by the Ethics Committee because patients reported no pain or limitations after Khalifa therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Sensitivity and specificity of MRI are limited to 85–95% which may lead to wrong positive and wrong negative results [23, 24]. This has to be considered, even if Ihara reported very good validity of MRI to diagnose ACL lesions [3, 11, 25–27]. Arthroscopy as the current diagnostic gold-standard was not authorized by the Ethics Committee because patients reported no pain or limitations after Khalifa therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal management of a torn ACL is still unknown [1]. When associated with knee instability the, injury may limit the level of activity [2, 3]. Conventional knowledge states that the ACL does not heal spontaneously after a complete rupture [46].…”
Section: Introductionmentioning
confidence: 99%
“…All of the patients in the series by Monaco et al [12] and Chun et al [1] with the preoperative cyclops had a partial tear. Only the series by Servien [17] found more complete than partial tears.…”
Section: Discussionmentioning
confidence: 99%
“…It involves an estimated 3 % of ACL tears [20] and often results in a loss of knee extension that may be mistakenly attributed to pain, post‐traumatic joint effusion or the presence of meniscal fragments. According to some authors, this lesion is usually found in partial tears [1, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Partial ruptures to the ACL may result in locking, although this is uncommon [4,7,8]. Accurate clinical examination is essential as the presence of intra-articular impingement necessitates urgent arthroscopy.…”
Section: Introductionmentioning
confidence: 99%